On-farm evaluation of fodder trees and shrubs preferred by farmers in central Kenya - Roothaert, Ralph L.; Franzel, Steven; Kiura, M. (Cambridge University Press, 2003)
The small amount of on-farm research that has been carried out with fodder trees in Africa has mainly involved exotic species selected by researchers rather than farmers. In this study, farmers who had participated in a pre-planting survey chose, during feedback meetings, seedlings of indigenous, naturalized and some exotic fodder trees from a nursery. They planted them on-farm, where the planting niches, management, biomass production, and animal response were evaluated over a short period, and compared with the results of the earlier survey. The farmers came from three agro-ecological zones in central Kenya with respective mean annual rainfall totals of 775, 950 and 1300 mm. Data were collected at two months, one year and two years after planting. The feedback meetings proved important to the understanding of discrepancies between the earlier survey results and farmers' practices. Survival and growth of seedlings, manure application by farmers, and percentage of trees pruned for fodder, differed among species. The farmers showed a strong interest in experimenting with and actively cultivating local fodder trees.